THE ROLE OF VISIONARY LEADERSHIP IN ENHANCING THE QUALITY OF LEADERS IN THE CAPACITY TO DEVELOP ISLAMIC EDUCATIONAL INSTITUTIONS - Real Vyanti Sjah, Novy; Rindaningsih, Ida (PT. Antis International Publisher, 2025)
Objective: This study aims to analyze the concept of visionary leadership in Islamic education, identify factors influencing leader quality, and explain the role of visionary leadership in developing Islamic educational institutions. It seeks to propose a model that integrates Islamic values with modern educational management to enhance institutional effectiveness. Methods: A qualitative approach with a literature study method was employed. Data collection involved analyzing books, scientific articles, and research reports related to visionary leadership and Islamic education. Thematic analysis was conducted to identify patterns and relationships among concepts, followed by the systematic presentation of findings. Results: The study highlights that visionary leadership, rooted in Islamic values, plays a critical role in educational transformation. Key factors influencing leader quality include managerial skills, communication abilities, and moral integrity. Visionary leadership fosters educational innovations, enhances learning quality, and strengthens stakeholder relationships. Moreover, it bridges academic goals with the spiritual and moral aspects inherent in Islamic education. The integration of Islamic values—such as honesty and compassion—into leadership practices supports the holistic development of students and institutional culture. Novelty: This research proposes a model of visionary leadership tailored to Islamic educational institutions. It emphasizes Islamic value-based management, systematic leader development strategies, and the incorporation of modern technology. The model is designed to address current challenges while maintaining the Islamic identity of institutions, providing actionable recommendations for leadership training and curriculum development responsive to local and global needs.